Factors affecting development of air ambulance base: A systematic review and thematic analysis - Zahra Eskandari; Zohreh Ghomian; Sanaz Sohrabizadeh; Ahmad Alibabaei; Hojjat Ahmadinejad (Wolters Kluwer Medknow Publications, 2021)
Nowadays, air ambulances have been developed as part of advanced emergency medicine services with many countries employing these services for transferring patients in usual and emergency conditions. However, there are challenges concerning the optimal development of air ambulance base. The present research aimed to identify factors affecting the development of air ambulance bases to provide the opportunity of planning to improve the quality of emergency medical services. In this systematic literature review, the peer-reviewed papers in fiv electronic databases, including Medline through PubMed, Scopus, Web of Science, ScienceDirect, and ProQuest, as well as available gray literature, were searched and selected. Two combinations of groups were used as keywords: the Health Planning and development factor, air ambulance base. The focus was on the PRISMA checklist, with no time limitations until from 1990 to January 2020. Finally, through 5156 related citations, 20 articles were included. Descriptive and thematic content analyses were evaluated. The factors affecting the development of the air ambulance base were classified in fiv categories and 14 subcategories as follows: navigation criteria, process indications and standards, sociopolitical factors, and current situation of the area. There are few studies on factors affecting the development of air ambulance bases. It is necessary to apply multidimensional models to consider various factors for development. The development of high populated cities, events and ceremonies with a crowd of participants, and increase of human-made disasters are making these services increasingly indispensable.